Análise comparativa do comportamento da corrosão em conectores de estacas-prancha metálicas laminadas a quente e conformadas a frio - Silva, Márcio Hartemink da (Universidade do Vale do Rio dos Sinos, 2016)
There are two models of steel sheet piles distinguished by its manufacturing process, one hot-rolled and the other cold formed. The main difference between them is its connection. The hot rolled steel sheet pile has an interlock connection and the cold formed steel sheet pile has a “hook” connection. As these elements are used in contact with the ground and water, there are concerns regarding its resistance to corrosion. The present paper proposes an analysis of the corrosion behavior in these two types of connectors. This paper reports the results of a corrosion behavior analysis in both types of connectors, as these are the most vulnerable parts of the steel sheet pile for corrosion. It was done a comparative analysis of the microscopic appearance of samples from both steel sheet piles before and after exposure to a combination of Salt Spray Test and immersed in chloride solution. Furthermore, tensile tests were carried out on samples to determine the impact of connection resistance.
Keywords: Durabilidade de estacas-prancha; Resistência à corrosão; Estacas-prancha laminadas a quente; Estacas-prancha conformadas a frio; Steel sheet pile; Connector; Corrosion; Hot rolled; Cold formed